The conflict management styles adopted by managers in an FET College in South Africa - Kwatubana, Siphokazi; Bosch, Mark (Penerbit Universiti Kebangsaan Malaysia, 2022)
The purpose of this study was to investigate the conflict management styles (CMSs) adopted by managers in an FET college in South Africa and the extent to which they were implemented. It contributes to the body of literature regarding the importance of advancement of conflict management skills to reduce the major barriers affecting the delivery of skills development in FET colleges. The research design and methodology were quantitative in nature, using a stratified sampling method yielding two strata of data: lecturers (junior and senior); and managers (heads of departments and managers at selected colleges). A structured questionnaire, with closed-ended questions, was administered to elicit information from 300 participants. Data were analyzed by means of descriptive statistics. The empirical findings revealed poor communication about conflict, a strong preference and over reliance on two CMSs which seemed to have resulted from lack of conflict management skills. In addition, the procedures and processes used in the two CMSs were perceived ineffective. The results also suggest that the efforts of the management in resolving conflict were thwarted by lack of communication. This study intensifies the discourse on conflict management in FET Colleges in South Africa which still grapple with inadequacy in providing quality and efficient service. The conclusion for this study is that there is a need to augment our understanding of CMSs and processes that influence how managers move from efforts to eliminate conflict. The role requirements of a manager require the use of different conflict management styles in order to be effective.